Bireycilik ve Yeni Kariyer Yönelimleri(Individualism and New Career Orientations) - Barış SEÇER; Efe ÇINAR (Yönetim ve Ekonomi, 2011)
This research examines the relationship between postgraduate students’ individualism values and their preferred career orientations. For this research, individualism was approached as a two-dimensional construct consists of horizontal and vertical dimensions. New career orientations were examined as boundaryless and protean careers. Vertical individualism values were found to be positively (cor)related with boundaryless mindset orientation and horizontal individualism values were found to be positively (cor)related with self-directed career orientation. After the regression analysis, it is determined that individualism levels drastically explain values driven career orientation.